2020
DOI: 10.1007/s00404-020-05730-z
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs expression profiling of rat ovaries displaying PCOS with insulin resistance

Abstract: Purpose The present study established microRNA (miRNA) expression profiles for rat ovaries displaying polycystic ovary syndrome (PCOS) with insulin resistance and explored the underlying biological functions of differentially expressed miRNAs. Methods A PCOS with insulin resistance rat model was created by administering letrozole and a high-fat diet. Total RNA was extracted from the ovaries of PCOS with insulin resistance rats and normal rats. Three ovaries from each group were used to identify differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In their study of key genes in resveratrol-induced apoptosis in porcine ovarian granulosa cells, Zhang et al found that the pathways signi cantly enriched were all associated with hormone secretion and metabolic pathways [26]. Zhang et al studied miRNA expression spectra in the ovary of rats with insulin resistance polycystic ovary syndrome (PCOS) and found that the predicted target genes correlated with metabolism pathways and that metabolism pathways were the richest pathways in KEGG enrichment analysis, which is consistent with our ndings [27]. In contrast, Su study of genes and their associated signalling pathways before and after primordial follicle initiation in mice found that differential target genes involved in ovarian follicle development were more enriched in the MAPK signalling pathway [28].…”
Section: Discussionsupporting
confidence: 88%
“…In their study of key genes in resveratrol-induced apoptosis in porcine ovarian granulosa cells, Zhang et al found that the pathways signi cantly enriched were all associated with hormone secretion and metabolic pathways [26]. Zhang et al studied miRNA expression spectra in the ovary of rats with insulin resistance polycystic ovary syndrome (PCOS) and found that the predicted target genes correlated with metabolism pathways and that metabolism pathways were the richest pathways in KEGG enrichment analysis, which is consistent with our ndings [27]. In contrast, Su study of genes and their associated signalling pathways before and after primordial follicle initiation in mice found that differential target genes involved in ovarian follicle development were more enriched in the MAPK signalling pathway [28].…”
Section: Discussionsupporting
confidence: 88%
“…miR-33b-5p is overexpressed in the ovarian tissue of insulin-resistant PCOS rats and therefore may play an important role in the development of insulin resistance in patients with PCOS (35). Another study found that miR-3585-5p and miR-30-5p were significantly upregulated and miR-146-5p was downregulated in the ovaries of rats with PCOS and insulin resistance (36). There are many changes in the expression of miRNA in the follicular fluid of patients with PCOS, and miR-127-3p has been found to be associated with insulin resistance (37).…”
Section: Discussionmentioning
confidence: 99%
“…We have identi ed micro-RNA species has-miR-21-5p, has-miR-335-5p, has-miR-146a-5p and has-miR-143-5p shared by the hub genes. These micro-RNAs have been linked to the development of PCOS [49][50][51] .…”
Section: Discussionmentioning
confidence: 99%